One hundred years of Colorado women - Bluemel, Elinor ([Place of publication not identified] : [Publisher not identified], 1973)
"The material for this book represents a brief compilation of events from the lives of twenty-seven women between 1876 and 1976 who have had enduring influence on Colorado, and sometimes even on the United States." -- first sentence of the preface.
Keywords: Women -- Colorado -- Biography; Colorado -- History